Influence of the growth characteristics and fabrication techniques on the mechanical properties of Pinus caribaea var. hondurensis timber glued-laminated beams - Ninin, Pablo; Contreras-Miranda, Wilver; Valero, Styles W. (Instituto de Ecología, A.C., 2016)
This paper is the culmination of a wide range of researches carried out at the Laboratorio Nacional de Productos Forestales, Mérida, Venezuela, focused on assessing the potentials of the Pinus caribaea var. hondurensis timber for the production of structural quality glued-laminated beams. Hence, the study allows determining, from the statistical analysis inference, the growth characteristics and fabrication techniques, the possible influences on the mechanical properties of glued laminated beams, especially the finger joints, with respect to the stress at Proportional Limit (ELP), Modulus of Rupture (MOR) and Modulus of elasticity (MOE). From the results, the influence of those defects can be determined in order of importance, which allows to get very concrete conclusions and recommendations to make the glued-laminated beam Venezuelan manufacturers reflect about the continuous improvement of their processes, products and services with the aim of keeping the supply of high quality and reliable structural products.